The Effect of WO3 Modification of ZrO2 Support on the Ni-Catalyzed Dry Reforming of Biogas Reaction for Syngas Production - Charisiou, Nikolaos D.; Siakavelas, Georgios; Papageridis, Kyriakos N.; Baklavaridis, Apostolos; Tzounis, Lazaros; Goula, Grammatiki; Yentekakis, Ioannis V.; Polychronopoulou, Kyriaki; Goula, Maria A. (Frontiers in Environmental Science, 2017)
The time-on-stream catalytic performance and stability of 8wt% Ni catalyst supported on two commercially available catalytic supports, ZrO2 and 15wt% WO3-ZrO2, was investigated under the biogas dry reforming reaction for syngas production, at 750oC and a biogas quality equal to CH4/CO2=1.5, that represents a common concentration of real biogas. A number of analytical techniques such as N2 adsorption/desorption (BET method), X-Ray diffraction (XRD), temperature programmed reduction (H2-TPR), temperature programmed desorption (NH3- and CO2-TPD), scanning electron microscopy (SEM), inductively coupled plasma emission spectroscopy (ICP), thermal analysis (TGA/DTG) and Raman spectroscopy were used in order to determine textural, structural and other physicochemical properties of the catalytic materials, and the type of carbon deposited on the catalytic surface of spent samples. These techniques were used in an attempt to understand better the effects of WO3-induced modifications on the catalyst morphology, physicochemical properties and catalytic performance. Although Ni dispersion and reducibility characteristics were found superior on the modified Ni/WZr sample than that on Ni/Zr, its dry reforming of methane (DRM) performance was inferior; a result attributed to the enhanced acidity and complete loss of the basicity recorded on this catalyst, an effect that competes and finally overshadows the benefits of the other superior properties.